2018
DOI: 10.1039/c8sc01263f
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamic nature of Mo sites for methane dehydroaromatization

Abstract: The dynamic catalytic site on Mo/HZSM-5 for methane dehydroaromatization is formed during the initial phases of the reaction. Labelling experiments show that carbon from the carbidic active site is incorporated into the final products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 53 publications
(56 reference statements)
12
96
0
Order By: Relevance
“…In contrast to that, we recently found that the carbon that is present at the active site itself plays an important role in activating methane equivalent to oxygen in the Mars‐van‐Krevelen mechanism . This is indicated by the fact that the carbon from the active site was found to be incorporated into the final products . In the iron catalyzed Fischer‐Tropsch synthesis, iron carbide initiates the hydrocarbon chain growth, and a similar mechanism can be envisaged for MDA.…”
Section: C−h Bond Activationmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast to that, we recently found that the carbon that is present at the active site itself plays an important role in activating methane equivalent to oxygen in the Mars‐van‐Krevelen mechanism . This is indicated by the fact that the carbon from the active site was found to be incorporated into the final products . In the iron catalyzed Fischer‐Tropsch synthesis, iron carbide initiates the hydrocarbon chain growth, and a similar mechanism can be envisaged for MDA.…”
Section: C−h Bond Activationmentioning
confidence: 97%
“…The chemical shift of 13 C MAS NMR and its anisotropy can yield information about carbidic Mo species forming at reaction conditions, but often the signal is dominated by a big contribution from carbonaceous deposits . We recently demonstrated that CO pretreatment results in an active site equivalent to the one formed at reaction conditions, but without the presence of any carbonaceous deposits . High resolution 13 C MAS NMR then revealed three different carbidic resonances: a sharp one stemming from Mo 2 C nanoparticles on the outer surface of the zeolite and two broad resonances corresponding to smaller species inside the pores of the zeolite.…”
Section: Understanding the Structure Of The Metal Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The majority of research on direct nonoxidative catalytic methane conversion deals with methane dehydroaromatization (MDA), and the most extensively studied catalyst for this purpose is Mo/HZSM‐5. Typically, 1 to 6 wt% of molybdenum loading is used . The number of studies focusing on nonoxidative conversion of methane to light hydrocarbons and olefins is relatively scarce compared with the number of studies on MDA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] Although the stoichiometry and coordination of MoC x clusters is still atopic of debate,the proficiency and reduced nature of active Mo-centers is no longer debated. [8,[10][11][12][13][14] Four noteworthy recent publications examine evolution and speciation of MoC x species in CH 4 DHA, [10,12,15,16] however, we make no effort to probe identity of MoC x species in this study and instead report in situ absorptive-hydrogen removal as as trategy to overcome thermodynamic limitations that limit single-pass conversion in CH 4 DHA to about 10 %. Arecent report proposes that addition of Zr metal as ah ydrogen absorber to MoO x /H-ZSM-5 formulations leads to increased CH 4 conversion and aromatic yields.…”
mentioning
confidence: 99%